122 P16 Immunohistochemistry Use in the Classification of Cervical Biopsies: Assessing Pathology Trainees' Diagnostic Proficiency. (11th January 2018) - Sultan, Kieran; Liu, Yuxin; Kalir, Tamara
Abstract: Objectives: In 2013, the nomenclature for human papillomavirus (HPV)-related lower anogenital squamous lesions was updated to a two-tiered system: high-grade squamous intraepithelial lesion (HSIL) vs low-grade squamous intraepithelial lesion (LSIL). LSIL represents transient HPV infection (CIN1); HSIL represents true cancer precursors (formerly CIN2/3). P16 immunohistochemistry (IHC) plays a critical role in the implementation of this new terminology. However, difficulties arise both in its judicious use and interpretation. Concerning p16 IHC use in grading cervical HPV-related lesions, we set out to determine pathology trainees' proficiency and interpretive skills with a goal of developing targeted, efficient training. Methods: Twelve pathology residents (PGY 2–5) participated in a survey of 20 cervical biopsies that included five unequivocal CIN1, five unequivocal CIN3, and 10 intermediate lesions (CIN2). We recorded trainees' initial H&E diagnosis (CIN1, CIN3, CIN2 requiring p16), frequency of p16 use, p16 interpretation (positive vs negative), and the final diagnosis (LSIL or HSIL) based on combined H&E and p16. Results: Based on H&E morphology, participants' initial diagnostic accuracy was 98% (59/60) for unequivocal CIN3 lesions, 72% (43/60) for unequivocal CIN1 lesions, and 57% (68/120) for CIN2 lesions. P16 IHC was required for an average of 48% of cases (range 30%-65%). Participants correctly interpreted 91% (42/46) of block-positive p16 patterns, 50% (5/10) of negative patterns, and 40% (28/69) of non-block positive patterns including weak/diffuse, strong/focal, and strong/basal stainings. Based on combined H&E and p16 IHC, participants' final diagnostic accuracy was 86% for HSIL and 72% for LSIL. Conclusion: Pathology trainees are up-to-date regarding current terminology and p16 applications. They are proficient in diagnosing unequivocal high-grade and low-grade lesions based on H&E morphology as well as interpreting block-positive p16 results. However, their skill deficiencies lie in handling morphologically intermediate lesions and interpreting non-block p16 staining patterns. We recommend enhanced training targeting these deficiencies.